Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To perform and simplify the operation
[tex]\[ \frac{16 x^3}{5 y^9} \cdot \frac{x^3 y^7}{80 x y^2}, \][/tex]
we start by breaking this down step-by-step.
1. Multiply the numerators:
[tex]\[ 16 x^3 \times x^3 y^7. \][/tex]
- Combine the [tex]\( x \)[/tex] terms:
[tex]\[ x^3 \times x^3 = x^{3+3} = x^6. \][/tex]
- Include the [tex]\( y \)[/tex] term:
[tex]\[ 16 x^3 \times x^3 y^7 = 16 x^6 y^7. \][/tex]
2. Multiply the denominators:
[tex]\[ 5 y^9 \times 80 x y^2. \][/tex]
- Combine the [tex]\( y \)[/tex] terms:
[tex]\[ y^9 \times y^2 = y^{9+2} = y^{11}. \][/tex]
- Include the [tex]\( x \)[/tex] term:
[tex]\[ 5 \times 80 x = 400 x. \][/tex]
Therefore,
[tex]\[ 5 y^9 \times 80 x y^2 = 400 x y^{11}. \][/tex]
3. Combine the fractions:
[tex]\[ \frac{16 x^6 y^7}{400 x y^{11}}. \][/tex]
Now we simplify the fraction by canceling common factors.
- Simplify the constants:
[tex]\[ \frac{16}{400} = \frac{16 \div 16}{400 \div 16} = \frac{1}{25}. \][/tex]
- Simplify the [tex]\( x \)[/tex] terms:
[tex]\[ \frac{x^6}{x} = x^{6-1} = x^5. \][/tex]
- Simplify the [tex]\( y \)[/tex] terms:
[tex]\[ \frac{y^7}{y^{11}} = y^{7-11} = y^{-4}. \][/tex]
4. Combining the results:
The simplified form of the given expression is:
[tex]\[ \frac{1 \times x^5}{25 \times y^{-4}} = \frac{x^5}{25 y^{-4}}. \][/tex]
Since [tex]\( y^{-4} = \frac{1}{y^4} \)[/tex]:
[tex]\[ \frac{x^5}{25 y^{-4}} = \frac{x^5}{25} \times y^4 = \frac{x^5 \times y^4}{25}. \][/tex]
Finally, the expression simplified is:
[tex]\[ \frac{x^5 y^4}{25}. \][/tex]
Therefore, the simplified form of the given fraction is:
[tex]\[ \frac{x^5}{25 y^{-4}}, \][/tex]
or equivalently,
[tex]\[ \frac{x^5}{25 y^{-4}} = 0 \equals 0. \][/tex]
[tex]\[ \frac{16 x^3}{5 y^9} \cdot \frac{x^3 y^7}{80 x y^2}, \][/tex]
we start by breaking this down step-by-step.
1. Multiply the numerators:
[tex]\[ 16 x^3 \times x^3 y^7. \][/tex]
- Combine the [tex]\( x \)[/tex] terms:
[tex]\[ x^3 \times x^3 = x^{3+3} = x^6. \][/tex]
- Include the [tex]\( y \)[/tex] term:
[tex]\[ 16 x^3 \times x^3 y^7 = 16 x^6 y^7. \][/tex]
2. Multiply the denominators:
[tex]\[ 5 y^9 \times 80 x y^2. \][/tex]
- Combine the [tex]\( y \)[/tex] terms:
[tex]\[ y^9 \times y^2 = y^{9+2} = y^{11}. \][/tex]
- Include the [tex]\( x \)[/tex] term:
[tex]\[ 5 \times 80 x = 400 x. \][/tex]
Therefore,
[tex]\[ 5 y^9 \times 80 x y^2 = 400 x y^{11}. \][/tex]
3. Combine the fractions:
[tex]\[ \frac{16 x^6 y^7}{400 x y^{11}}. \][/tex]
Now we simplify the fraction by canceling common factors.
- Simplify the constants:
[tex]\[ \frac{16}{400} = \frac{16 \div 16}{400 \div 16} = \frac{1}{25}. \][/tex]
- Simplify the [tex]\( x \)[/tex] terms:
[tex]\[ \frac{x^6}{x} = x^{6-1} = x^5. \][/tex]
- Simplify the [tex]\( y \)[/tex] terms:
[tex]\[ \frac{y^7}{y^{11}} = y^{7-11} = y^{-4}. \][/tex]
4. Combining the results:
The simplified form of the given expression is:
[tex]\[ \frac{1 \times x^5}{25 \times y^{-4}} = \frac{x^5}{25 y^{-4}}. \][/tex]
Since [tex]\( y^{-4} = \frac{1}{y^4} \)[/tex]:
[tex]\[ \frac{x^5}{25 y^{-4}} = \frac{x^5}{25} \times y^4 = \frac{x^5 \times y^4}{25}. \][/tex]
Finally, the expression simplified is:
[tex]\[ \frac{x^5 y^4}{25}. \][/tex]
Therefore, the simplified form of the given fraction is:
[tex]\[ \frac{x^5}{25 y^{-4}}, \][/tex]
or equivalently,
[tex]\[ \frac{x^5}{25 y^{-4}} = 0 \equals 0. \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.